Advances and challenges in targeting IRF5, a key regulator of inflammation - Almuttaqi, Hannah (FEBS J, 2018)
Interferon regulatory factor 5 (IRF5) belongs to a family of transcription factors, originally implicated in antiviral responses and interferon production. However, studies conducted in different laboratories over the last decade have placed IRF5 as a central regulator of the inflammatory response. It has become clear that IRF5 contributes to the pathogenesis of many inflammatory and autoimmune diseases, such as rheumatoid arthritis, inflammatory bowel disease and systemic lupus erythematosus. Given the role of IRF5 in physiology and disease, IRF5 represents a potential therapeutic target. However, despite a significant interest from the pharmaceutical industry, inhibitors that interfere with the IRF5 pathway remain elusive. Here, we review the advances made by various studies in targeting multiple steps of signalling leading to IRF5 activation with their therapeutic potential, and the possible complications of such strategies are discussed.